REPRESENTASI BUDAYA MATRILINEAL MINANGKABAU DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK - Trisnawati Trisnawati; Chelsy Yesicha (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
Film is a media of mass communication that still have audiences until now. Film also become a media of life representation. Researcher lift a film entitled Tenggelamnya Kapal Van Der Wijck. Tenggelamnya Kapal Van Der Wijck is a film that tell about the orphan man, Zainuddin. He has a Minangnese father and a mother from Makassar. Then he decided to move to his father hometown, Batipuh West Sumatra. As a person of mix descent, he faces much discrimination from Minang conservatives. Although he loves Hayati, a Minangnese woman, the niece of local nobleman, he’s not allowed to be with her because his background.The researcher method is cualitative that referring to semiotics analysis of Roland Barthes. The subject of the research is Minangkabau Matrilineal culture with research object is a Tenggelamnya Kapal Van Der Wijck Film. Data collection techniques using semiotic data analysis techniques by Barthes. On data validity techniques by extending participation and observational persistence.The result of this research show that scenes researched related with the meaning of denotation, connotation, and myth by Roland Barthes. And the result also shows that have the representation of Minangkabau Matrilineal Culture in Tenggelamnya Kapal Van Der Wijck that Minangkabau’s culture is too strict, also people claimed as a Minangnese only if their mother is a Minangnese even though their father is a Minangnese. And Mamak (mother’s brothers) has an authorization in their clan and to the nieces and nephews. And his authority is stronger than their own father.